TRANSFORMATIONAL LEADERSHIP DAN PENGARUHNYA TERHADAP KINERJA ANGGOTA ORGANISASI - Paulina Hani Rusmawati; Fibria Indriati (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2019)
The aims of the research is to realize the relationship between transformational leadership and employee performance through a mediating effect of work engagement. The approach used in this study is a quantitative approach, data collection techniques through questionnaires in the form of a likert scale. The population in this study were 30 employees of PT Kereta Api Indonesia in the Daerah Operasi 5 Purwokerto on Asset Guard and Regional Rail Bridge unit. The data analysis technique used in this study is using structural equation modeling (SEM) with the application of the smartPLS program. This study found that transformational leadership has a direct or indirect influence on organizational member performance, the work engagement variable is able to mediate the indirect influence between transformational ledership and the performance of organizational members.